Some Distinct Features of Transformative High Entropy Alloys for Metal Additive Manufacturing - Nene, S.S. (Frontiers in Materials, 2022)
Sudden damage in engineering materials during service was always a challenge and lot of efforts have been put forward by materials scientist to resolve this issue. This motivated the design of variety of classes of alloys such as stainless steel, deformed and partitioned steels, metastable Ti alloys and recently developed high entropy alloys (HEA). Continuous evolving journey from single phase to multi-phase HEAs showed exceptional work hardenability in them which is required for improved failure resistance in metallic systems. In line of that, recently developed transformative high entropy alloys (T-HEAs) displayed interesting outcomes in terms of improved damage tolerance (~1.2 GPa, 20% with 1.5% defect density) after conventional processing, severe deformation and laser assisted 3D printing. These outcomes were attributed to the localized work hardening activity within the stress concentration regions near the defects due to activation of transformation induced plasticity (TRIP). As a result, defects present in these T-HEAs were found to act as a sites for delaying the damage by showing pronounced transformation induced crack retardation (TRICR) effect thereby improving the failure resistance during service.